Taxonomy of Japanese Gonatopus (Hymenoptera: Dryinidae), with description of a new species - Mita, Toshiharu (Zootaxa, 2024)
A new species of Gonatopus, G. tagoi sp. nov., is described from Japan. Previously uncertain species, Agonatopus gracilis Esaki & Hashimoto, 1932 is redescribed based on newly collected females. Currently A. gracilis is included in Gonatopus, however, the name Gonatopus gracilis is preoccupied by Kieffer, 1905. Therefore, Gonatopus gigantostratiotes nom. nov. is provided as a replacement name. An updated key to the females of Japanese Gonatopus is given.